Morphology of Maxillary First Molars Analyzed by Cone-Beam Computed Tomography among Malaysian: Variations in the Number of Roots and Canals and the Incidence of Fusion - Al-Kadhim, Aws Hashim; Rajion, Zainul Ahmad; AB Malik, Normaliza; Jaafar, Azlan (IIUM Medical Journal Malaysia, 2017)
Introduction: A few studies investigated the numerous potential endodontic uses of CBCT, including the examination of root canal morphology and presumed that CBCT was effective for the initial identification of such morphology; moreover CBCT is a reliable method for the detection of the MB2 canal when compared with the gold standard of physical sectioning of the specimen. The aim of this study was to identify the root and canal morphology of the maxillary first molars among Malaysians analysed by cone-beam computed tomography (CBCT) images. Materials and Methods: Maxillary first (n = 421) molars from Malaysian patients (n = 241) of Malay, Chinese and Indians inceptions were examined by two Endodontists using in vivo CBCT methods. The number and configuration of roots, the number of root canals, and the canal configuration according to Vertucci’s classification were determined. Results: Single roots were not found in maxillary first molars. The incidence of fused roots was 1.995% in the first molars between mesiobuccal and distobuccal roots. In (421) 3-rooted maxillary first molars, additional canals were found in 45.6% of the mesiobuccal (MB) roots and 0% of the distobuccal (DB) roots. Bilateral symmetry of the MB roots was found in 82.36% of the first molar. Only one tooth was found to have pulp stone inside the pulp chamber. Conclusions: The root and canal configuration of a Malaysian population showed different features from those of other populations. CBCT scans can enhance the understanding of root canal anatomy, with the potential of improving the outcome of endodontic treatment.